A Multicontrolled Enamine Configurational Switch Undergoing Dynamic Constitutional Exchange. Issue 21 (2nd May 2018) - Ren, Yansong; Svensson, Per H.; Ramström, Olof
Abstract: A multiresponsive enamine‐based molecular switch is presented, in which forward/backward configurational rotation around the C=C bond could be precisely controlled by the addition of an acid/base or metal ions. Fluorescence turn‐on/off effects and large Stokes shifts were observed while regulating the switching process with Cu II . The enamine functionality furthermore enabled double dynamic regimes, in which configurational switching could operate in conjunction with constitutional enamine exchange of the rotor part. This behavior was used to construct a prototypical dynamic covalent switch system through enamine exchange with primary amines. The dynamic exchange process could be readily turned on/off by regulating the switch status with pH. Abstract : Switched on : An enamine‐based molecular switch operating under a multiple dynamic regime is presented. The forward and backward configurational rotation could be controlled by an acid/base, as well as by metal coordination, which was associated with fluorescence turn‐on/off effects with Cu II (see picture). The switching could also operate in conjunction with constitutional enamine exchange of the rotor part of the switch.